2020
DOI: 10.3389/fenrg.2020.00037
|View full text |Cite
|
Sign up to set email alerts
|

Methanogenesis Inhibition in Anaerobic Granular Sludge for the Generation of Volatile Fatty Acids from CO2 and Zero Valent Iron

Abstract: A new approach for CO 2 utilization (as a sole carbon source) to acetic acid and other VFAs under ambient conditions using zero valent iron and anaerobic granular sludge was examined by methanogens inhibition. Zero Valent Iron when is anaerobically oxidized generates H 2 that can be utilized along with CO 2 by homoacetogens in the anaerobic granular sludge for the production of acetic acid or other VFAs. However, methanogens in anaerobic sludge act antagonistically with homoacetogens and therefore the main goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“… Chakraborty et al (2020) demonstrated enhanced ethanol production from C 1 gas by granular sludge and Clostridium autoethanogenum was successfully enriched at 33°C. Similarly, Samanides et al (2020) reported an increased relative abundance of Clostridium of 65.9% in anaerobic granular sludge for acetic acid production, when first exposed to heat (95°C for 30 min) and incubated with 100% CO 2 and 100 g/L zero valent iron at 33°C.…”
Section: Discussionmentioning
confidence: 83%
“… Chakraborty et al (2020) demonstrated enhanced ethanol production from C 1 gas by granular sludge and Clostridium autoethanogenum was successfully enriched at 33°C. Similarly, Samanides et al (2020) reported an increased relative abundance of Clostridium of 65.9% in anaerobic granular sludge for acetic acid production, when first exposed to heat (95°C for 30 min) and incubated with 100% CO 2 and 100 g/L zero valent iron at 33°C.…”
Section: Discussionmentioning
confidence: 83%
“…Thus, the analysis of prokaryotic community structures shaped by pH conditions revealed the positive and negative selection of VFA producers and consumers, respectively, as well as the in silico prediction of metabolic functions—based on prokaryotic community structures—suggest that the development of fermentation conditions inhibiting methanogenesis and/or stimulating carbohydrate utilization can be a further practicable strategy to improve the production of VFA [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…For all anaerobic experiments, sealed glass serum bottles were used and were incubated at 37 • C. Anaerobic granular sludge was used at a concentration of 4% w/v, collected from a mesophilic upflow anaerobic sludge blanket reactor (UASB) that was treating dairy wastewater (Charalambides Christis Ltd, Limassol, Cyprus), operated at pH 6.8-7.3 (as reported by Samanides et al, 2020). Raw bilge wastewater was used, collected by a company treating this wastewater type (Ecofuel Ltd, Zygi, Cyprus), the wastewater characteristics are described in detail in a previous study by Vyrides et al (2018b).…”
Section: Anaerobic Digestion Of Bilge Wastewatermentioning
confidence: 99%